Effectiveness of a family customised online FOCUS programme aimed on building resiliency in dyad relationship to support dyadic illness management in persons with heart failure and their informal caregiver: a randomised clinical trial protocol. Issue 7 (27th July 2022) - Yang, Weiling; Cao, Yongjun; Li, Yanting; Zhang, Xiaonan; Li, Xuedong; Jiang, Sixuan; LV, Qingyun; Cheng, Mei; Zhang, Xin; Zang, Xiaoying
Abstract : Introduction: Living with heart failure (HF), is a shared journey and arduous work for patients and their informal family caregivers. Given the key role and limited evidence of dyad illness management in improving dyad health in the context of HF, we developed a customisable, relationship focused, family online dynamic disease management programme—FOCUS programme—to improve dyad health for HF patients and their informal caregivers in China. Methods and analysis: Based on the Theory of Dyadic Illness Management and the Systemic Transactional Model of Stress and Coping, the family customised online FOCUS programme has five modules: (1) family participatory; (2) open communication; (3) coping effectiveness; (4) uncertainty reduction and 5) shared dyad life stories. HF family dyads will be recruited in the cardiology wards of four university-affiliated hospitals in China. The dyads (N=142) will be randomly allocated to the intervention group that will receive the family customised online FOCUS programme, and the attention control group that will not receive elements of the FOCUS programme. Dyadic coping, HF somatic perception, self-care, anxiety and depression for patients and family caregivers and all-cause mortality and hospital admission for patients will be measured at baseline, 4 weeks (after the discharge, T1), 12 weeks (after the discharge, T2) and 24 weeks (after the discharge, T3). Statistical analysis will be performed using SPSS V. 22.0 software. Ethics and dissemination: The study protocol was approved by the ethics committees of Tianjin Medical University (Reference number TMUHEC2019002) that covers all the centres enrolled in this study. The findings of this study will be published in scientific journals and will be presented at scientific conferences. Trial registration number: ChiCTR2100053168.